The Relationship Between Reading Skills and Intelligence in Students With and Without Special Educational Needs in Learning - Scholz, Markus; Scheer, David (Frontiers in Education, 2020)
Reading research shows that phonological decoding skills and intelligence work mostly independent from each other. However, there is a variety of results on the relationship between reading skills and IQ measures. Studies in this field mainly focus on students with reading disabilities (RD) or students with intellectual disabilities (ID) and less on pupils with Special Educational Needs in Learning (SEN-L). We performed a secondary data analysis to evaluate differences in reading skills and fluid intelligence between students with (N=144) and without (N=157) SEN-L and the relationship between SEN-L, reading skills and fluid intelligence. Participants completed a standardized screening of reading skills (SLS 2-9) and a German culture fair intelligence test (CFT 20-R). Students with SEN-L had lower scores in both tests. Correlations between both scores were smaller within the two groups than in the total sample. Implications of the findings are discussed.